The role of the junctional zone in the management of adenomyosis with infertility - Wang, Sha; Duan, Hua (Frontiers in Endocrinology, 2023)
The junctional zone (JZ) is an important structure in the myometrium that maintains uterine fertility. Changes in the junctional zone are closely related to infertility and adenomyosis (ADS). As an increasing number of young women are affected by ADS, the disease is no longer considered typical of women over 40. With these changes, a increasing number of patients refuse hysterectomy and desire fertility preservation treatment. At the same time, ADS is a crucial factor causing female infertility. Therefore, the treatment of ADS-related infertility and preservation of reproductive function is one of the other major challenges facing clinicians. For these young patients, preserving fertility and even promoting reproduction has become a new challenge. Therefore, we searched and summarized these studies on PubMed and Google Scholar using keywords such as "adenomyosis", "junctional zone", and "infertility" to explore infertility causes, diagnosis, and treatment of ADS patients who wish to preserve their uterus or fertility and become pregnant, focusing on the junctional zone, to obtain a full appreciation of the new perspective on this disease.